Comment est née et a survécu la revue « Assurances » - Parizeau, Gérard (Assurances, 1982)
The Author, founder and director of this publication, recalls how it was born and progressed throughout the years. ''Assurances" till now has been very much alive because of his determination, courage and tenacity along with extensive knowledge of insurance per se. His great talent as a writer naturally completed the requirements for success. Numerous faithful collaborators have also contributed to keep up interest, along with our subscribers. These pages contain a perfect blend of numerous anecdotes through which one captures the visionary soul of the author that he always was and still is.